2004
DOI: 10.1080/08958370490428436
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Ozone, Diesel Exhaust Particles, and Standardized Ambient Particulate Matter in Rats with aListeria Monocytogenes-Induced Respiratory Infection

Abstract: Ambient particulate matter may increase respiratory allergic skewing of the T-cell-mediated immune response toward a T-helper-2 (Th2) response, with the consequence that the Th1 response develops less well. Successful clearing of a respiratory bacterial infection depends on an adequate Th1 immune response; therefore, the subject would not control the infection as well if exposed to particulate matter. To substantiate this hypothesis, we examined the effect of exposure to diesel exhaust particles (DEP) and urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…In contrast to the findings discussed above, Steerenberg et al (2004) found that intranasal administration of DEP and EHC-93 (urban particulate matter collected in Ottawa, Canada) had no effect on the ability of rats to clear L. monocytogenes infection up to 5 days post-infection in both the lungs and the spleen, indicating that the immune system was not altered by the particulate exposure. Interestingly, ozone was used as a positive control in their study, and as expected, exposure to ozone (1 ppm) significantly impaired clearance of the bacteria from the rat lungs and spleen.…”
Section: Dep Modulation Of Susceptibility To Infectioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In contrast to the findings discussed above, Steerenberg et al (2004) found that intranasal administration of DEP and EHC-93 (urban particulate matter collected in Ottawa, Canada) had no effect on the ability of rats to clear L. monocytogenes infection up to 5 days post-infection in both the lungs and the spleen, indicating that the immune system was not altered by the particulate exposure. Interestingly, ozone was used as a positive control in their study, and as expected, exposure to ozone (1 ppm) significantly impaired clearance of the bacteria from the rat lungs and spleen.…”
Section: Dep Modulation Of Susceptibility To Infectioncontrasting
confidence: 80%
“…These results suggest that although high doses of DEP affected the immunological response to infection, the animals were still able to effectively counter the infections. Several studies found dose-dependent effects on susceptibility to infection extending to much lower DEP concentrations (30 µg/m 3 ), but Steerenberg et al (2004) notably found no significant effects of DEP exposure on clearance of L. monocytogenes infection with lower DEP exposure levels. Overall, the implications of the observed immunological effects in animals for human exposures are not entirely clear.…”
Section: Dep Modulation Of Susceptibility To Infectionmentioning
confidence: 94%
“…Additionally, PAH and quinone play a key role in the activation of SAPKs, which regulate the expression of proinflammatory genes in macrophages (12), thus suggesting that oxidative stress is one of the mechanisms by which DEPs exert their toxic effects in the lungs. DEPs may, independently or in association with other material, present many diverse effects, including the decrease in alveolar macrophage function (35), impairment of mucociliary clearance, modification of the surfactant composition (10) and secretion (19), among other deleterious effects. Laks and coworkers (13) reported that metals and sulfur components of diesel affected particle toxicity to a lesser extent than its organic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the DEF group of defense and immunity proteins underwent significant changes, with changes that included roughly equal numbers of increases and decreases. This "mixed" response may explain why ozone exposure has been reported to prime pulmonary innate immunity, and thereby enhance the response to LPS [111], while impairing clearance of pathogens that are dependent upon removal by cell-mediated immune mechanisms, including Listeria monocytogenes or Klebsiella pneumoniae [9,112]. There is precedent for selective changes in susceptibility.…”
Section: Proteome Of Wt Micementioning
confidence: 99%